Soil carbon sequestration potential and the identification of hotspots in the eastern Corn Belt of the United States. Issue 5 (1st September 2021) - Grace, Peter; Robertson, G. Philip
Abstract: Soil C sequestration is a significant CO2 mitigation strategy, but precise assessments of sequestration require spatially explicit modeling of potential changes in soil organic C (SOC) in response to soil, climate, land condition, and management interactions. We assessed the SOC sequestration potential of the eastern Corn Belt (ECB) in the United States (Indiana, Kentucky, Maryland, Michigan, Ohio, Pennsylvania, and West Virginia) in response to the adoption of conservation farming practices and land use change (pasture and forestation) using the SOCRATES model. Input data was provided through an intersection of the State Soil Geographic database, National Land Cover Database, and a PRISM (https://prism.oregonstate.edu) climate surface. At the end of the 20th century, the 15.3 Mha of cropped soils in the ECB contained 632 Tg C, an estimated reduction of 52% since the introduction of agriculture in the mid 1800s. Complete adoption of no‐tillage practices on prime cropland would potentially recover 147 Tg SOC over 20 yr, whereas a continuation of conventional tillage would produce a loss of 35 Tg SOC over that period. Sequestration hotspots (>500 Gg increase in SOC) under no‐tillage cover 2.3 Mha providing 28 Tg C over 20 yr. The conversion of marginal (nonprime) agricultural lands to forests would yield an additional 13 Tg C in SOC and 381 Tg C in aboveground biomass. The rehabilitation of minelands to forest would yield an additional 4 Tg C in SOC and 42 Tg C in biomass. Opportunities to sequester C in the ECB via tillage and reforestation are substantial and should be incorporated into regional and national climate change mitigation strategies. Core Ideas: Soil organic C (0–30 cm) in the eastern Corn Belt croplands declined by 52% (632 Tg) since the mid 1800s. No‐tillage practices on prime cropland potentially recovers 147 Tg soil C over 20 yr. Soil organic C sequestration hotspots (>500 Gg C increase) under no‐tillage cover 2.3 Mha and produce 28 Tg C.